2020
DOI: 10.9779/pauefd.523545
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Matematik Öğretim Programı Dersi Kazanımlarının Yenilenen Bloom Taksonomisine Göre İncelenmesi

Abstract: Bu araştırmanın amacı, İlkokul Matematik Öğretim Programında yer alan kazanımların Yenilenmiş Bloom Taksonomisine göre taksonomik düzeylerini belirlemektir. Araştırmada nitel araştırma yaklaşımı benimsenmiş olup, araştırma verileri doküman incelemesi yoluyla elde edilmiştir. Araştırma verileri, 2018 yılında güncellenen İlkokul Matematik Dersi Öğretim Programı kazanımlarından elde edilmiştir. Çalışmada 2018 yılında yayınlanan İlkokul Matematik Dersi Öğretim Programında (1. -4.sınıflar) yer alan 229 kazanımın Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
1
11
0
13
Order By: Relevance
“…When the studies of the curriculum of different courses are examined, it is seen that there are similar results. In his study, Aktan (2020) determined that the 1th-4th-grade course outcomes in the primary school mathematics curriculum are concentrated in lower levels such as practice, understanding and remembering, which includes low-level cognitive steps. Duman and Arslan (2017) concluded that the attainments in the logic course curriculum are outside the two dimensions (creation dimension and metacognitive knowledge dimension).…”
Section: Discussionmentioning
confidence: 99%
“…When the studies of the curriculum of different courses are examined, it is seen that there are similar results. In his study, Aktan (2020) determined that the 1th-4th-grade course outcomes in the primary school mathematics curriculum are concentrated in lower levels such as practice, understanding and remembering, which includes low-level cognitive steps. Duman and Arslan (2017) concluded that the attainments in the logic course curriculum are outside the two dimensions (creation dimension and metacognitive knowledge dimension).…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, it is possible to put forward that 3 rd -grade LSCC in 2018 concentrates on basic cognitive process skills and objectives for high-level cognitive process skills are not represented enough in the curriculum. A literature review reveals that other curriculum analyses carried out in primary school (Aktan, 2020;Aslan & Atik, 2018;Buyukalan Filiz & Baysal, 2019;Canguven, Oz, Binzet, & Avci, 2017;Durmus, 2017;Karip, 2019;Yolcu, 2019) are like LSCC within that respect. Although this finding is consistent with the literature review, a LSCC based on constructivist approach is supposed to support the learning of high-level cognitive process skills (Biggs, 1996;Driscoll, 1994).…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…When the studies of the curriculum of different courses are examined, it is seen that there are similar results.In his study, Aktan (2020) determined that the 1-4th grade course outcomes in the Primary School Mathematics Curriculumare concentrated in lower levels such as practice, understanding and remembering, which includes low-level cognitive steps. Duman and Arslan (2017) concluded that the attainments in the logic course curriculum are outside the two dimensions (creation dimension and metacognitive knowledge dimension).…”
Section: Discussionmentioning
confidence: 99%